MOSEL survey: extremely weak outflows in EoR analogues at z = 3−4. Issue 1 (5th December 2022) - Gupta, Anshu; Tran, Kim-Vy; Mendel, Trevor; Harshan, Anishya; Forrest, Ben; Davies, R L; Wisnioski, Emily; Nanayakkara, Themiya; Kacprzak, Glenn G; Kewley, Lisa J
ABSTRACT: This paper presents deep K-band spectroscopic observations of galaxies at z = 3 − 4 with composite photometric rest-frame H β +[O iii ] 5007 equivalent widths (EW0 ) > 600 Å, comparable to the EW of galaxies observed during the epoch of reionization (EoR, z > 6). The typical spectroscopic [O iii ] 5007 EW0 and stellar mass of our targets is ∼700 Å and log ( M * /M⊙ ) = 8.98. By stacking the [O iii ] 5007 emission profiles, we find evidence of a weak broad component with $\rm F_{broad}/F_{narrow} \sim 0.2$ and velocity width σbroad ∼ 170 km s −1 . The strength and velocity width of the broad component does not change significantly with stellar mass and [O iii ] 5007 EW0 of the stacked sample. Assuming similar broad component profiles for [O iii ] 5007 and Hα emission, we estimate a mass loading factor ∼0.2, similar to low stellar mass galaxies at z > 1 even if the star formation rates of our sample is 10 times higher. We hypothesize that either the multiphase nature of supernovae driven outflows or the suppression of winds in the extreme star-forming regime is responsible for the weak signature of outflows in the EoR analogues.